Fóruns educacionais: estratégias de interação em uma disciplina do curso de letras da ufpb virtual - Aragao, Jackelinne Maria de Albuquerque (2011)
Distance Education constitutes, nowadays, a teaching modality of growing importance. Therefore, a study focused on the strategies used by tutors, professors and students aiming at interaction in the distance educational forums, was done. In order to develop the research, the study was theoretically based on Bakhtin´s/Volochinov´s (1929/2010) and Bakhtin´s (2006) perspectives, taking into account their language concept, discursive genres, enunciation, dialogism, active responsive comprehension and verbal interaction. The theoretical basis regarding Distance Education, as well as the professor´s, the tutor s and the student s profile, in the virtual learning environment, were focused on Belloni´s (2003) and on Palloff´s & Pratt´s (2004) assumptions. The research is considered as being of qualitative nature (BOGDAN & BIKLEN, 1999; GODOY, 1995) and of netnographic basis (VERGARA, 2005), once the researcher is part of its private locus. With the intention to start the investigation, some of the interaction sessions were analyzed. Such interactions occurred, from March to December 2010, and they are related to a subject of the third term of the Licentiate Course in Letters of the Virtual UFPB. In this respect, the strategies identified in the interactions among the interlocutors such as professor, tutor and student in the Doubt Forum, Thematic Forum, and the Coffee Forum were categorized. The results demonstrate the need for (1) the professor interlocutor to boost dialogic learning through the use of interaction strategies which promote major reflection, questioning, movements of retake and synthesis in a constant dialogue of voices, that (2) the distance tutor can develop a partnership work with the student, contributing to a transition from the notion of knowledge assimilation to the interaction notion and joint construction and that (3) the student interlocutor can develop enunciation exchanges concerning a major use of sayings that reflect inquiries, questionings and problems, perceiving, equally, the importance of interaction between student-student while constructing collectively the Virtual Learning Environment.